Concentration-dependent spectroscopic properties and temperature sensing of YNbO4:Er3+ phosphors. Issue 38 (3rd May 2017) - Wang, Xin; Li, Xiangping; Cheng, Lihong; Xu, Sai; Sun, Jiashi; Zhang, Jinsu; Zhang, Xizhen; Yang, Xiaotian; Chen, Baojiu
Abstract : Er 3+ concentration had significant influences on temperature sensitivity. The sample with a low concentration of Er 3+ had high temperature sensitivity. Abstract : A series of YNbO4 :Er 3+ phosphors with various Er 3+ concentrations was synthesized via a traditional high temperature, solid-state reaction method. XRD Rietveld refinements based on the XRD data were carried out to study the phase purity and crystal structure of the as-prepared samples. The results revealed that single monoclinic phase YNbO4 phosphors were obtained. The influence of the Er 3+ concentration on the spectroscopic properties and temperature sensing in YNbO4 :Er 3+ phosphors were systematically studied. Different quenching concentrations were found in down-conversion and up-conversion luminescence processes. From lasers working current dependent up-conversion luminescence spectra, it was confirmed that two and three photon processes were responsible for both the green and the red up-conversion emissions, respectively, excited by 980 and 1550 nm lasers, which have no apparent dependence on Er 3+ ion concentration. However, the Er 3+ concentration had significant influences on the temperature sensing sensitivity of Er 3+ ions, and the results showed that YNbO4 phosphors doped with low concentrations of Er 3+ ions had high temperature sensing sensitivity and could be applied in temperature detection applications, particularly in high temperature environments.